War and Trade in Eighteenth-Century Newfoundland. - Janzen, Olaf Uwe, 1949- (Research in Maritime History LUP., 2017)
This book offers a selection of papers by Olaf U. Janzen concerning the maritime history of eighteenth-century Newfoundland, reprinted from various publications and assembled here in chronological order. It explores themes of imperial dominance expressed by both the British and French empires in the struggle for sovereignty that ensconced the two nations.